Teaching English for Tertiary Students in Pesantren: A Narrative during and Post Pandemic COVID-19 - Irsyadi, Achmad Naufal; Muta'allim, Muta'allim (JET ADI BUANA, 2023)
The problem in English learning is determining how learners and teachers adjusted to remote learning methods. This study identified and evaluated the English learning difficulties encountered by students in non-English departments. This study included students from five different academic programs, namely Islamic Education (PAI), Management of Islamic Education (MPI), Akhwalusy Syakhshiyah (AS), Primary School Teacher Education (PGMI), and Islamic Banking (PS). The qualitative research was used in this study, along with a phenomenological approach. The data were obtained from a questionnaire through Google Form to students in these departments. The questionnaire discussed challenges that students had when learning English with an online system, materials that students did not grasp, and students' expectations for English language learning. The data were analyzed by including several research and ideas related to previously formulated materials in the questionnaire. This study was supposed to be taken into account while developing techniques and strategies for English language acquisition for non-English students in higher education. This study resulted that the dominant problems faced by respondents were online learning systems (54.8%), and applications used as learning media (29%). Other problems included limited internet network access, difficulty in understanding English courses, lack of detailed material exposure, and laziness.